Influence of Shrinkage on Air and Water Vapour Permeability of Double-Layered Weft Knitted Fabrics - Asta BIVAINYTĖ; Daiva MIKUČIONIENĖ (Medžiagotyra, 2012)
Water vapour permeability and transport depends on the properties of the fibre and knitted fabric structure. It was designed double-layered fabrics knitted in plain plating pattern whose inner side was  made from synthetic fibres the PES, PA, PP, and Coolmax® (tetra-channel fibres by DuPont) which do not absorb moisture and on the surface of the wear – natural cotton and bamboo fibres which have good absorption properties. In the present research it was established that the air permeability of all fabrics after washing and drying cycle decreased. It occurred because of the influence of shrinkage during washing and drying under the impact of moisture, heat, and mechanical action. After washing and drying cycle, the water vapour permeability of fabrics knitted from bamboo and synthetic yarns blend decreased predominantly and became similar to fabrics knitted from cotton and respective synthetic yarns blend. The water vapour permeability of fabrics knitted from cotton and synthetic yarns blend decreased significant less. Depending on the knitting structure, the most decrease of water vapour permeability was estimated to the plain plated fabrics. DOI: http://dx.doi.org/10.5755/j01.ms.18.3.2438